2010
DOI: 10.1134/s1021443710050080
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterial rol genes modify thermodynamic and structural properties of starch in microtubers of transgenic potato

Abstract: INTRODUCTIONTuber formation in potato is regulated by numerous external and internal factors with phytohormones being of special importance [1]. In order to investigate the hormonal control over tuber formation, some researchers used transformed potato plants expressing rolB and rolC genes of Agrobacterium rhizogenes [2]. Biochemical mechanism of the operation of rol trans genes remains debatable; however, it was shown that their role in higher plants resembles to the effect of phytohormones: auxins in case ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…As regards our starch samples, the melting temperature increased in KCl solution by 1.8-2.2 • K, values typical for B-type of a polymorphic structure. Together with previous WAXS data (Aksenova et al, 2010;Wasserman et al, 2014), this indicates that the polymorphic starch structure did not change in transgenic plants under different growth conditions.…”
Section: Properties Of Potato Starches From In Vivo Grown Tuberssupporting
confidence: 82%
See 1 more Smart Citation
“…As regards our starch samples, the melting temperature increased in KCl solution by 1.8-2.2 • K, values typical for B-type of a polymorphic structure. Together with previous WAXS data (Aksenova et al, 2010;Wasserman et al, 2014), this indicates that the polymorphic starch structure did not change in transgenic plants under different growth conditions.…”
Section: Properties Of Potato Starches From In Vivo Grown Tuberssupporting
confidence: 82%
“…However, we have previously shown by Х-ray scattering and DSC that such a change was not observed in case of rol transformants (Aksenova et al, 2010). Also the expression of AtPHYB did not change the polymorphic structure of starches.…”
Section: Properties Of Potato Starches From In Vitro Grown Tubersmentioning
confidence: 69%
“…The thermogram curves of extracted starches are exemplified in Figure 6. It should be noted that the profile of thermograms for all the studied samples was typical for native potato starches [19,[33][34][35][36]; therefore, not all thermograms are demonstrated. The endothermic peak on DSC thermograms is characterized by temperature transition (T melt ), which is associated with endothermic, cooperative, irreversible thermodynamic transition known as gelatinization [37].…”
Section: Starch Thermodynamic Propertiesmentioning
confidence: 93%
“…It is likely that ectopic expression of the PHYB gene from Arabidopsis thaliana increases the occurrence of defects in comparison with starch from non-transgenic tubers [19,33], which leads to differences in the thermodynamic parameters of starch melting from tubers upon their prolonged rest. This effect is observed in plants grown both in vitro and in vivo.…”
Section: General Considerationsmentioning
confidence: 99%
“…The in fl uence of rol genes on carbohydrate metabolism has seldom been studied, even in other plant systems. When rolB and rolC gene-transformed potato microtubers were analyzed, the structure of the starch granules were very different in each case from those of normal tubers (Aksenova et al 2010 ) , indicating the commercial importance of such gene interactions. The selective secretion of proteins such as peroxidase enzymes from red beet hairy roots (Thimmaraju et al 2005(Thimmaraju et al , 2007 has demonstrated the inherent secretory nature, which is yet another phenomenon worth characterizing for commercial exploitation in the context that hairy roots ably synthesize human proteins and other animal proteins (Kang et al 2011 ;Guillon et al 2006 ) .…”
Section: Red Beet Hairy Roots For Morphophysiological Studiesmentioning
confidence: 95%